The nucleus accumbens as a nexus between values and goals in goal-directed behavior: a review and a new hypothesis - Mannella, Francesco; Gurney, Kevin; Baldassarre, Gianluca (Frontiers in Behavioral Neuroscience, 2013)
Goal-directed behaviour is a fundamental means by which animals can flexibly solve the challenges posed by variable external and internal conditions. Recently, the processes and brain mechanisms underlying such behaviour have been extensively studied from behavioural, neuroscientific and computational perspectives. This research has highlighted the processes underlying goal-directed behaviour and associated brain systems including prefrontal cortex, basal ganglia and, in particular therein, the nucleus accumbens. This paper focusses on one particular process at the core of goal-directed behaviour: how motivational value is assigned to goals on the basis of internal states and environmental stimuli, and how this supports goal selection processes. Various biological and computational accounts have been given of this problem and of related multiple neural and behaviour phenomena, but we still lack an integrated hypothesis on the generation and use of value for goal selection. This paper proposes an hypothesis that aims to solve this problem and is based on this key elements: (a) amygdala and hippocampus establish the motivational value of stimuli and goals; (b) prefrontal cortex encodes various types of action outcomes; (c) nucleus accumbens integrates different sources of value, representing them in terms of a common currency with the aid of dopamine, and thereby plays a major role in selecting action outcomes within prefrontal cortex. The ‘goals’ pursued by the organism are the outcomes selected by these processes. The hypothesis is developed in the context of a critical review of relevant biological and computational literature which offer it support. The paper shows how the hypothesis has the potential to integrate existing interpretations of motivational value and goal selection.